(untitled) (Nexo Revista Científica, 2022)
Supercritical fluid extraction is a rapid, selective, and environmentally friendly method of particular interest in the extraction of essential oils from plants and herbs. Curcuma zedoaria is a member of the Zingiberaceae family widely cultivated in India, China, and Southeast Asia, including Vietnam. This study examined the chemical composition and antimicrobial activity of essential oils from the leaves and rhizomes of C. zedoaria from Vietnam obtained via supercritical fluid extraction. The main compounds of leaf essential oil were iso-borneol (31.2%), β-elemene (14.7%), β-caryophyllene (11.4%), 1,8-cineole (9.7%), and caryophyllene oxide (5.9%). In rhizome essential oil, 1,8-cineole (41.7%), β-elemene (13.6%), curzerenone (12.3%), camphor (10.2%), and germacrene B (5.2%) comprised the main compounds. The essential oils from C. zedoaria leaves and rhizomes displayed antimicrobial activity against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus cereus, and Candida albicans, with minimum inhibitory concentration values ranging from 100–400 µg/mL. Thus, our results support the need for further investigation of C. zedoaria essential oils as a potential source of antimicrobial agents.